Карнавальне колесо постмодерністської деконструкції в текстах-подорожах М. Кідрука “Мексиканські хроніки” та Я. Рудницького “Тричі так!” - Кропивко, І. (Слово і Час, 2018)
Вияви деконструктивізму постмодерністської художньої прози спрямовані на деструкцію ідеологем і карнавально-ігрове конструювання нових текстів із їхніх уламків. Тексти про персонажа, який подорожує, використовують тип людини-номада та відповідають принципам безперервного руху без початку й кінця як основи життя й тимчасовості значень. Цими принципами вони перегукуються з бахтінським образом карнавального колеса змішування й додавання значень, їхньої аієрархічності. М. Кідрук (“Мексиканські хроніки”) переосмислює усталені поняття, зв'язки між поняттями та “грається” ролями, у яких виступає його наратор. Я. Рудницький (“Тричі так!”) більше уваги приділяє змішуванню ціннісних параметрів, понять сакрального і профанного, мертвого і живого, верху і низу. The subject of the research is destruction of the grand narrators’ ideologemes of the modern era and the specific character of carnival in the analyzed texts. The paper outlines the key features in the authors’ attempt of making the artistic world look like carnival, and pays attention to the notional structure of their works. The researcher’s methodology combines comparative analysis with elements of deconstruction and semiotics. The novelty of the research consists in demonstrating the carnival way of thinking of postmodern writers in prose travel-texts. It is found out that the carnival postmodern way of writers’ thinking is shown in destructing the established hierarchy of the values and in constructing the new artistic meanings on their basis. The genre model of travelogue implements the postmodern carnival principle of non-selection. It includes various types of text (artistic, non-fiction, journalistic reports), media (word, visualization) and multifunctional narrator (narrator, traveler, interlocutor). Ukrainian (M. Kidruk) and Polish (J. Rudnicki) writers also use the principles of carnival mixing of values and abundance. M. Kidruk pays much attention to the various types of information given to the reader by the narrator. J. Rudnicki applies the principle of abundance for unfolding the plot and uses anecdotic episodes. Texts under analysis tend to focus on reproducing the subjective and versatile world of the mental journey of the narrator. Of course, this journey is connected to geographical reality and its emotional comprehension. Проявления деконструктивизма постмодернистской художественной прозы нацелены на деструкцию идеологем и карнавально-игровое конструирование новых текстов из их обломков. Тексты о путешествующем персонаже используют тип человек а-номада и соответствуют принципам беспрерывного движения без начала и конца как основы жизни и временности значений. Этими принципами они перекликаются с бахтинским образом карнавального колеса смешения и добавления значений, их аиерархичности. М. Кидрук (“Мексиканские хроники”) переосмысливает устоявшиеся понятия, связи между понятиями и “играет” ролями, в которых выступает его нарратор. Я. Рудницкий (“Трижды так!”) больше внимания уделяет смешению ценностных параметров, понятий сакрального и профанного, мертвого и живого, верха и низа.